Persepsi Karyawan Tentang Kode Etik Perusahaan (Studi Kasus Pada PT Astra Internasional Tbk, Daihatsu Cabang Malalayang Manado) - Virnia R. L. D. Adilang; Riane J. Pio; Sandra I. Asaloei (JURNAL ADMINISTRASI BISNIS, 2018)
The purpose of this study is "To describe how employee perceptions about the application of corporate code of ethics at PT Astra International Tbk. Daihatsu Branch Malalayang Manado ". Benefits in this research is this research is expected to be used as additional reference material for further research and add references of library in department of Administration Science especially Business Administration study program and expected to be used as base and consideration of useful input for company leader and employee at PT. Astra International Tbk, Daihatsu Branch Malalayang Manado. This research uses quantitative method. Data obtained from this research is data through interviews and distribution of questionnaires distributed to all employees. The results of this study indicate that employees' perceptions about the company's code of ethics are seen as important, positive, and beneficial to employees as well as corporate leaders, in performing their duties and fulfilling their respective responsibilities to companies. And, states that the code of ethics that has been applied to the company is working properly. Most employees expressed their view that the code of ethics that has been applied to the employee is satisfactory, the company also treats its employees vaguely without specializing by looking at it in any way. This is evidenced through tabulation of data and scoring of the results that can pass the division of questionnaires. Therefore it can be concluded that most employees agree with the code of ethics that has been applied by the company.